Intergalactic Absorption Confounding Circumgalactic Observations - Itai Bromberg; Kartick C. Sarkar; Haggar Ashkenazy; Orly Gnat; Yuval Birnboim (The Astrophysical Journal)
The origin of warm ions in the circumgalactic medium (CGM) surrounding massive galaxies remains a mystery. In this paper, we argue that a significant fraction of the observed warm-ion columns may arise in the intergalactic medium (IGM) surrounding galactic halos. We use a simple spherical collapse model of the dark matter halos and their baryonic content to compute the evolving ion fractions within and outside virial halos. We show that the photoionized IGM may produce a thick blanket of warm ions around the CGM, with column densities comparable to observed values near galaxies, which may therefore contaminate CGM observations. We compare our results with observations, and find that our models qualitatively reproduce the overall O vi columns as well as their trend with the impact parameter and halo mass. We find that the IGM contribution to the observed column depends on galaxy mass and impact parameter, and becomes comparable to the total observed values in galaxies with virial masses exceeding a few times 10 ^11 M _⊙ , as well as across much of the observed area ( b ≳ 0.5 R _vir ) of lower-mass halos. We therefore suggest that theoretical interpretations of CGM-survey observations must consider the possible contribution of the surrounding IGM. We note that more sophisticated (3D) models are required to consider the possibility of nonunity covering fractions suggested by the data. Although our simplified model suggests that it may be possible to kinematically distinguish between CGM and IGM origins through the absorption-line profiles, this distinction is likely unfeasible.